Opioid Receptor-Mediated Regulation of Neurotransmission in the Brain - Reeves, Kaitlin C.; Shah, Nikhil; Muñoz, Braulio; Atwood, Brady K. (Frontiers in Molecular Neuroscience, 2022)
Opioids mediate their effects via opioid receptors: mu, delta, and kappa. At the neuronal level, opioid receptors are generally inhibitory, presynaptically reducing neurotransmitter release and postsynaptically hyperpolarizing neurons. However, opioid receptor-mediated regulation of neuronal function and synaptic transmission is not uniform in expression pattern and mechanism across the brain. The localization of receptors within specific cell types and neurocircuits determine the effects that endogenous and exogenous opioids have on brain function. In this review we will explore the similarities and differences in opioid receptor-mediated regulation of neurotransmission across different brain regions. We discuss how future studies can consider potential cell-type, regional, and neural pathway-specific effects of opioid receptors in order to better understand how opioid receptors modulate brain function.